Smokeless tobacco, snus, at admission for percutaneous coronary intervention and future risk for cardiac events. Issue 2 (15th October 2019) - Frobert, Ole; Reitan, Christian; Hatsukami, Dorothy K; Pernow, John; Omerovic, Elmir; Andell, Pontus
Abstract : Objective: To assess the risk of future death and cardiac events following percutaneous coronary intervention (PCI) in patients using smokeless tobacco, snus, compared with patients not using snus at admission for a first PCI. Methods: The Swedish Coronary Angiography and Angioplasty Registry is a prospective registry on coronary diagnostic procedures and interventions. A total of 74 958 patients admitted for a first PCI were enrolled between 2009 and 2018, 6790 snus users and 68 168 not using snus. We used Cox proportional hazards regression for statistical modelling on imputed datasets as well as complete-case datasets. Results: Patients using snus were younger (mean (SD) age 61.0 (±10.2) years) than patients not using snus (67.6 (±11.1), p<0.001) and more often male (95.4% vs 67.4%, p<0.001). After multivariable adjustment, snus use was not associated with the primary composite outcome of all-cause mortality, new coronary revascularisation or new hospitalisation for heart failure at 1 year (HR 0.98, 95% CI 0.91 to 1.05). In patients using snus at baseline who underwent a second PCI (n=1443), the duration from the index intervention was shorter for subjects who continued using snus (n=921, 63.8%) compared with subjects who had stopped (mean number of days 285 vs 406, p value=0.001). Conclusions: Snus use at admission for a first PCI was not associated with a higher occurrence of all-cause mortality, new revascularisation or heart failure hospitalisation. Discontinuing snus after a first PCI was associated with a significantly longer duration to a subsequent PCI.